The AGNIFS survey: spatially resolved observations of hot molecular and ionized outflows in nearby active galaxies. Issue 2 (24th February 2023) - Riffel, R A; Storchi-Bergmann, T; Riffel, R; Bianchin, M; Zakamska, N L; Ruschel-Dutra, D; Bentz, M C; Burtscher, L; Crenshaw, D M; Dahmer-Hahn, L G; Dametto, N Z; Davies, R I; et al.
ABSTRACT: We present the hot molecular and warm ionized gas kinematics for 33 nearby (0.001 ≲ z ≲ 0.056) X-ray selected active galaxies using the H_2 2.1218 μ m and Br γ emission lines observed in the K band with the Gemini near-infrared integral field spectrograph. The observations cover the inner 0.04–2 kpc of each active galactic nucleus at spatial resolutions of 4–250 pc with a velocity resolution of σinst ≈ 20 km s^-1 . We find that 31 objects (94 per cent) present a kinematically disturbed region (KDR) seen in ionized gas, while such regions are observed in hot molecular gas for 25 galaxies (76 per cent). We interpret the KDR as being due to outflows with masses of 10 2 –10 7 and 10 0 –10 4 M⊙ for the ionized and hot molecular gas, respectively. The ranges of mass-outflow rates (M_out ) and kinetic power (E_K ) of the outflows are 10 −3 –10 1 M⊙ yr −1 and ∼10 37 –10 43 erg s −1 for the ionized gas outflows, and 10 −5 –10 −2 M⊙ yr −1 and 10 35 –10 39 erg s −1 for the hot molecular gas outflows. The median coupling efficiency in our sample is E_K/L_bol≈ 1.8× 10^-3 and the estimated momentum fluxes of the outflows suggest they are produced by radiation-pressure in low-density environment, with possible contribution from shocks.